Application of nanoparticles for salinity stress management and biofortification in wheat: a review of dual approaches and insights - Singh, Abhishek; Bol, Roland; Lovynska, Viktoriia; Singh, Rupesh Kumar; Sousa, João Ricardo; Ghazaryan, Karen (Frontiers in Plant Science, 2025)
Salinity stress is one of the most challenging constraints affecting wheat production, limiting both yield and nutritional quality. Wheat is one of the most important staple cereals as well as a major source of carbohydrates for a considerable portion of the world population, yet wheat has suffered from significant productivity constraints due to salt stress. Such stress adversely affects germination, vegetative growth, reproductive organ development, enzymatic activity, photosynthesis photostability, and hormonal equilibrium, eventually causing oxidative stress and drastic loss of crop yield. Furthermore, the reducing nutritional quality of wheat further aggravates the issues regarding malnutrition and food security, highlighting the need for effective mitigation strategies. Although various methods have been investigated, including plant breeding, genetic engineering, and agronomic management, they are labor, cost, and time-intensive. Nanotechnology is a novel, eco-friendly and efficient approach for controlling salinity stress and improving crop biofortification. Some common methods of applications of nanotechnology-based products like nanoparticles (NPs) are foliar spraying, soil amendments and seed priming, which have shown considerable promise in improving salinity stress resistance, nutrient absorption, and wheat yield. This review outlines the extent of contribution of NPs in alleviating salinity stress, as well as the enhancement of the nutritional qualities of wheat. This work uniquely combines both salinity stress adaptation and nanofortification strategies under one framework that filling crucial information gaps. Investigating the mechanisms underlying NPs interaction with plant systems is essential for designing effective, green, and cost-efficient nanotechnology tools for sustainable wheat production. In the long run, this knowledge will aid sustainable agricultural practices and food security worldwide.